Automatic detection system of interested news topic - Hanief Mumtazul Anwar (Nanyang Technological University, 2022)
In the age of digital information, countless news articles are published on the internet every day. News articles in digital formats published by various publishers consists of multiple topics, from sports, technology, politics, natural disasters, etc. Individuals have different preferences in following a news topic development. Text classification could be implemented to perform news topic categorization, so that news is categorized based on its topic and people could easily select the news based on the topic that they want to follow. However, there are no platform that provides news articles from multiple trusted publishers, and filters the list based on the news topic. This project aims to perform news topic categorization, and develop an application that able to provides user with news articles based on its topic.